2022
DOI: 10.1002/jcla.24763
|View full text |Cite
|
Sign up to set email alerts
|

HSPA6, a novel prognostic and therapeutic biomarker, associated with Ming classification in gastric cancer

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…HeatMap revealed that IL7R, LTB, HSPA6, TYROBP, and TRDV2 were enriched in the clusters. Numerous studies have confirmed that IL7R, [12][13][14] HSPA6, [15][16][17] and TYROBP 18,19 are closely associated with human cancers, which suggests that T cells possess a strong ability of EC.…”
Section: Identification Of T Cell Marker Genes Expression Profilesmentioning
confidence: 95%
“…HeatMap revealed that IL7R, LTB, HSPA6, TYROBP, and TRDV2 were enriched in the clusters. Numerous studies have confirmed that IL7R, [12][13][14] HSPA6, [15][16][17] and TYROBP 18,19 are closely associated with human cancers, which suggests that T cells possess a strong ability of EC.…”
Section: Identification Of T Cell Marker Genes Expression Profilesmentioning
confidence: 95%